1993
DOI: 10.1063/1.354609
|View full text |Cite
|
Sign up to set email alerts
|

Strong blue light emission from an oxygen-containing Si fine structure

Abstract: A photoluminescence study has been made on an oxygen-containing Si fine structure fabricated by a gas evaporation technique. Transmission electron micrographs have shown that the fine structure is composed of nonspherical particles aggregated together in chain-like or cluster-like structures. The luminescence from the samples after oxidation treatment is bright blue as viewed with the naked eye, the spectra having a peak at about 470 nm or shorter wavelength. A peculiar temperature dependence of the emission p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(15 citation statements)
references
References 9 publications
2
13
0
Order By: Relevance
“…In the first material group Morisaki et al found a 2.64-eV peak (E ex = 3.35 eV) for Si-rich deposited oxides [42]. When studying nanocrystalline Si Zhao et al obtained PL peaks at 2.67, 2.84 and 2.98 eV under 3.68 or 3.82 eV excitation.…”
Section: Luminescence Of Ion-implanted Sio 2 Layersmentioning
confidence: 98%
“…In the first material group Morisaki et al found a 2.64-eV peak (E ex = 3.35 eV) for Si-rich deposited oxides [42]. When studying nanocrystalline Si Zhao et al obtained PL peaks at 2.67, 2.84 and 2.98 eV under 3.68 or 3.82 eV excitation.…”
Section: Luminescence Of Ion-implanted Sio 2 Layersmentioning
confidence: 98%
“…3,4 Because the blue color is also crucial to the Si-based full-color display, some other methods are attempted to achieve blue emission. [5][6][7][8][9] SiO 2 films are extensively used in silicon devices and integrated circuits as passivation layers and electrical insulation layers. Their optical properties have been investigated.…”
mentioning
confidence: 99%
“…Other alternative methods have been proposed to produce silicon nanocrystals: plasma deposition from silane, 9 gas evaporation, 10 and termination of glass-melt reaction. 11 These techniques have been demonstrated capable of producing visible-light emission at room temperature, but still none of them seems appropriate for the production of integrated devices.…”
mentioning
confidence: 99%